Chinese art - Tregear, Mary 1924- (London Thames and Hudson Ltd, 1997)
Traces the history of Chinese painting and sculpture, and describes important movements and themes.
Neolithic crafts (c. 5th millennium-18th century BC) -- Hieratic art and the Bronze Age (18th-12th centuries BC) -- Status and decoration (12th-3rd centuries BC) -- Nationalism and expression (3rd century BC-3rd century AD) -- The imprint of Buddhism (1st-10th centuries) -- Internationalism and showmanship (4th-10th centuries) -- Space and monumentality (10th-early 12th centuries) -- Court and Chan Buddhist arts (early 12th-early 14th centuries) -- Tradition and Invention (14th-15th centuries) -- Eclecticism and innovation (15th-17th centuries) -- Individualism and eccentricity (17th-18th centuries) -- Enquiry and dislocation (19th-20th centuries).
162 illustrations, 21 in colour.
Includes bibliographical references (page 201) and index.
Keywords: Art, Chinese